A reverse-engineered pitch on defensive versus evidence-based medical technology: Liability risk and electronic fetal monitoring in low-risk births - Elizabeth Yong; Kun Hing Yong (Journal of Accounting and Management Information Systems (JAMIS), 2023)
This pitching research letter (PRL) describes the application of the pitching research template introduced by Faff (2015, 2021) to a reverse-engineering process in the practice of electronic fetal monitoring (EFM) as a form of defensive medicine with regard to the field of medical technology. The pitch structure underlines a succinct and streamlined approach to recapitulate key components of scientific studies that form the basis upon which a researcher's scientific or seminal research work is assembled.
Keywords: K32; N7; 650; Pitching Research; Reverse Engineering Pitch; Medical Technology; Defensive Medicine; Electronic Fetal Monitor